Dataset supporting the estimation and analysis of high spatial resolution inventories of atmospheric emissions from several sectors in Argentina - Puliafito, Salvador Enrique (2020)
This data article provides an extensive and complete description of the high spatial resolution inventory (HSRI) estimation shown in the article “High resolution inventory of atmospheric emissions from livestock production, agriculture, and biomass burning sectors of Argentina” Puliafito et al. [1], and its comparison with several sectors in Argentina. The dataset provided are highresolution inventories (0.025 0.025 lat/long) for CO2, CH4, N2O and another 8 species from livestock, biomass burning, agriculture and another 12 sectors (based on 2016 year). In addition, we also provide the database for 2014 using the same methodology. The dataset presented are necessary to improve input inventories for air quality models. Also, they are better to inform and guide the stakeholders, in making decisions related to environmental protection and health promotion, as well as assessing the environmental performance in terms of atmospheric emissions of an activity, sector or region in Argentina